Legal Protection For House Buyers Subsidies Against Development Who Is Declared In Bankruptcy - Dewi, Nurcahya Sukma Kusuma; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to identify and analyze the legal protections for buyers of subsidized houses against tenants who are declared bankrupt, identify and analyze the weaknesses of legal protection for binding subsidized houses and their solutions, and identify and analyze examples of binding deed of selling and buying subsidized houses. The approach method in this research is a normative juridical approach, the research specification is descriptive analytical. The data required includes primary data taken by the literature study method. The data analysis method used descriptive qualitative analysis method. Based on the research concluded that the weakness of the legal protection for binding subsidized housing is that there is no standard implementation arrangement regarding legal protection that will be given to consumers who always place the consumer as a weak party because they have submitted a certain amount of money as a down payment and some have started the mortgage payment process without receiving the subsidized housing unit. While the usual solution is for consumers to add some money for the completion of public facilities, such as roads, independently which has not been completed by the developer or receive some money as a substitute for the down payment that has been submitted without receiving the promised unit.